MORPHOLOGY OF DIAMONDS DISSOLVED IN THE Fe-S MELT AT DIFFERENT SULFUR CONTENTS - V. M. SONIN; I. A. GRYAZNOV; E. I. ZHIMULEV; A. I. CHEPUROV (Известия высших учебных заведений: Геология и разведка, 2018)
An experimental study of the process of the dissolution of diamonds in a sulfur-containing iron melt with different contents of sulfur (10,  15, 20, 25, 30 wt. %) at 3,5 GPa and 1400°C has been carried out.  The obtained results indicate that under the realized conditions, the  plane-faced diamond crystals of octahedral habit are transformed  into a curved octahedroid shape with morphological characteristics similar to  natural diamonds from kimberlites. It has been concluded that metal- sulphide melts, given their relatively low melting points, could affect the  safety of diamonds in the mantle. The presence of sulfur reduces  the solubility of carbon and tends to zero in the Fe-S melt compositions  close to eutectic (25 and 30 wt. %). That is, the presence of sulfur has a favorable effect on the stability of diamonds.